301 Effects of housing system on performance and behavior of dairy calves before and after weaning. (5th December 2019) - Liu, Shuai; Alugongo, Gibson; Li, Jinghui; Cao, Zhijun; Wang, Yajing; Li, Shengli
Abstract: The aim of this study was to evaluate the effects of housing system on performance and behavior of dairy calves during pre-weaning (d 1–42), weaning (d 43–56), post-weaning (d 57–63) and mixing (d 64–70) period. Thirty-seven newborn Holstein dairy calves were allocated to individual (n = 17) or pair housing (n = 10 pairs). After that, calves remained in their pens until d 63 ± 1, and then PH group and IH group were mixed and moved to 6 group pens randomly. Starter intake, fecal consistency scores and body weight were collected. Instantaneous scan-sampling with 5-min intervals was used to collect the behavioral observations (lying, ruminating, standing, eating, drinking, walking, self-grooming, manipulating object) for 48 h beginning on d 43, 50, 57 and the second day after mixing. Data were analyzed by mixed effect model with treatment, time, and the interaction between them as fixed effects, and animal within treatment as a random effect. During post-weaning period, PH group had higher starter intake (P = 0.02) and average daily gain (P = 0.02) than IH group. PH group weighed more on d 63 (P = 0.002) and d 70 (P = 0.002). PH group had higher diarrhea frequency than IH group in week 3 (P = 0.03). PH increased lying time in week 8 (P = 0.03) and walking time during post-weaning period (P = 0.05), yet IH group spent more time standing in week 8 (P = 0.008), eating during post-weaning period (P = 0.008), self-grooming during weaning period (week 7, P = 0.007; week 8, P = 0.03). Furthermore, previous housing system had no effect on calves' behavior after mixing. In conclusion, Pair housing during post-weaning period improved performance of calves and housing system had on effect on behavior after mixing.